Návrh na rozšíření funkcí elektronických cenovek přispívající k lepší komunikaci se zákazníkem - Petýrková, Pavlína (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Tématem této diplomové práce je návrh na rozšíření funkcí elektronických cenovek přispívající k lepší komunikaci se zákazníkem. Práce je rozdělena do tří částí – teoretické, analytické a návrhové. Teoretická část vychází z odborné literatury a je klíčová k hlubšímu porozumění problematiky. Zároveň slouží jako opora pro analytickou část. V jejím úvodu je představena společnost DATART. Analytická část se zabývá zodpovězením dílčích výzkumných otázek prostřednictvím rozhovorů, dotazníkového šetření a pozorováním. V části návrhové jsou na základě výsledků analýz vytvořeny návrhy soustřeďující se na konkrétní opatření a strategie, které naplní definované cíle.

The topic of this thesis is a proposal to expand the functionalities of electronic shelf labels to enhance communication with customers. The thesis is divided into three parts – theoretical, analytical, and proposal. The theoretical part is based on professional literature and is crucial to a deeper understanding of the issue. It also serves as a basis for the analytical part. In its introduction the company DATART is presented. The analytical part then deals with answering partial research questions interviews, questionnaire survey and observation. Based on the results of the analysis, the proposal part develops proposals focusing on specific measures and strategies that will meet the defined objectives.
Proposal for the Extension of the Functionality of Electronic Shelf Labels for the Improvement of Communication with Customers
Keywords: Aplikace; benchmarking; elektronická cenovka; elektronika; ESL; inovace; marketing; marketingová strategie; retail; technologie; Application; benchmarking; electronic shelf label; electronics; ESL; innovation; marketing; marketing strategy; retail; technology